Why d-Mannose May Be as Efficient as Antibiotics in the Treatment of Acute Uncomplicated Lower Urinary Tract Infections-Preliminary Considerations and Conclusions from a Non-Interventional Study - Florian Wagenlehner; Horst Lorenz; Oda Ewald; Peter Gerke (MDPI AG, 2022)
Urinary tract infections (UTIs) are very frequent in women and can be caused by a range of pathogens. High recurrence rates and increasing antibiotic resistance of uropathogens make UTIs a severe public health problem. d-mannose is a monosaccharide that can inhibit bacterial adhesion to the urothelium after oral intake. Several clinical studies have shown the efficacy of d-mannose in the prevention of recurrent UTIs; these also provided limited evidence for the efficacy of d-mannose in acute therapy. A recent prospective, non-interventional study in female patients with acute cystitis reported good success rates for treatment with d-mannose. Here, we present data from a post hoc analysis of this study to compare the cure rate of d-mannose monotherapy with that of antibiotics. The results show that d-mannose is a promising alternative to antibiotics in the treatment of acute uncomplicated UTIs in women.